The effect of long term administration of glucocorticoid to bone lining cells apoptosis - Sari, Gadis Meinar (Folia Medica Indonesiana, 2017)
Glucocorticoid is widely used in medical treatment as an immune system or an inflammation therapy. However its long term administration can cause life-threatening side effects. One of them is bone mass loss which increases the risk of bone fractures in the long-term use. Bone lining cells derived from mesenchymal stem cells, which serve as a backup cell bone-forming osteoblasts. Glucocorticoids acting directly on osteoblasts, bone lining cells when reduced due to increased apoptosis, the reserve cells to bone formation will be decreased. The aim of this study was to count the amount of apoptotic bone lining cells after long term glucocorticoid administration. This study used Rattus norvegicus females aged 3 months that were divided into 3 groups, each group consisted of 7 rats. The groups are: (1) control group; (2) treatment group 1 were given glucocorticoid 0.01 mg/day; (3) treatment group 2 were given glucocorticoid 0.2mg/day. The treatment carried out for 4 weeks and at the end of treatment, rats were sacrified and continued with preparation, and the number of bone lining cells that undergoing apoptosis was calculated through examination of the femur bone tissue metaphysis section using immunohistochemical technique. All data were analyzed with statistical analysis Anova. The result showed that the number of apoptotic bone lining cells increased in group with glucocorticoid administration 0.01 mg/day and 0.2 mg/day compared to control group with p = 0.000 (p <0.05). The number of apoptotic bone lining cells on the group of glucocorticoid dose 0.2 mg/day higher than the group of glucocorticoid dose 0.01 mg/day with p = 0.000 (p <0.05). In conclusion, long term glucocorticoid administration increase apoptosis of bone lining cells.